Principal component regression in GAMLSS applied to Greek–German government bond yield spreads. (February 2022) - Mikis, D. Stasinopoulos; Robert, A. Rigby; Nikolaos, Georgikopoulos; Fernanda, De Bastiani
A solution to the problem of having to deal with a large number of interrelated explanatory variables within a generalized additive model for location, scale and shape (GAMLSS) is given here using as an example the Greek–German government bond yield spreads from 25 April 2005 to 31 March 2010. Those were turbulent financial years, and in order to capture the spreads behaviour, a model has to be able to deal with the complex nature of the financial indicators used to predict the spreads. Fitting a model, using principal components regression of both main and first order interaction terms, for all the parameters of the assumed distribution of the response variable seems to produce promising results.